Urban Structure and its Modern Transformation in Kathmandu City - Ranjitkar, Nanda Gopal (Himalayan Review, 2011)
Available with fulltext. Key words: Structure; Transformation; Cultural landscape; Functional principle; Water spout; Kathmandu city The Himalayan Review Nepal Geographical Society Vol. XXXI, 2000 Page: 60-80 Uploaded date: 5 June, 2011